Investment in Human Capital and its Efficiency - Šileika, Algis; Tamašauskienė, Zita (Ekonomika, 2003)
In this article, investment in human capital are analysed. Costs and benefits of investment in human capital are presented. The costs consist of direct costs and indirect costs, in the form of foregone earnings of not entering the labor market after secondary school, minus the resources made available to students in the form of grants and loans. The benefits are the gains in post-tax earnings minus the repayment, if any, of public support during the period of study.Using cost-benefit model the authors estimated private rates of return to university and nonuniversity higher education. The estimation results show that private internal rates of return to university education in Lithuania arc higher than the real interest rate of return on other productive assets and equal 12,87 per cent, suggesting that human capital investment is an attractive way for an average person to build up wealth. The internal private rate of return to university education in Lithuania is 5,63 percentage points lower than in United States, but it is 6,35 percentage points higher than in Italy. Although private rate of return to nonuniversity higher education is 2,69 percentage points lower than to university education, it is also high, and demonstrates that there are strong incentives for an average student to engage in education activity. The authors prove that earnings differentials and the length of education are the prime determinants of the private internal rates of return.The benefits of higher education to society are assessed on the basis of social rates of return, which reflect the costs and benefits of investment in education to society. Estimation results show that in Lithuania social rate of return is lower than private rate of return by 1 percentage point, however it is high, suggesting that investment in education is a productive use of public funds.